Predictable Alteration of Sequence Recognition by RNA Editing Factors from Arabidopsis. Issue 2 (3rd February 2015) - Kindgren, Peter; Yap, Aaron; Bond, Charles S.; Small, Ian
Abstract : Experimental evidence shows that plant RNA editing factors bind RNA via contiguous modular one-motif:one-nucleotide interactions and that sequence recognition can be altered using simple rules. Abstract: RNA editing factors of the pentatricopeptide repeat (PPR) family show a very high degree of sequence specificity in the recognition of their target sites. A molecular basis for target recognition by editing factors has been proposed based on statistical correlations but has not been tested experimentally. To achieve this, we systematically mutated the pentatricopeptide motifs in the Arabidopsis thaliana RNA editing factor CLB19 to investigate their individual contribution to RNA recognition. We find that the motifs contributing significantly to the specificity of binding follow the previously proposed recognition rules, distinguishing primarily between purines and pyrimidines. Our results are consistent with proposals that each motif recognizes one nucleotide in the RNA target with the protein aligned parallel to the RNA and contiguous motifs aligned with contiguous nucleotides such that the final PPR motif aligns four nucleotides upstream of the edited cytidine. By altering S motifs in CLB19 and another editing factor, OTP82, and using the modified proteins to attempt to complement the respective mutants, we demonstrate that we can predictably alter the specificity of these factors in vivo.